2005
DOI: 10.1007/bf03030568
|View full text |Cite
|
Sign up to set email alerts
|

Genome constitution and classification using retrotransposon-based markers in the orphan crop banana

Abstract: We have exploited the repetitive and dispersed nature of many long terminal repeat (LTR)-retrotransposon families for characterizing genome constitutions and classifying cultivars of the genus Musa. Insertional polymorphisms of the elements were studied using seven published and two newly designed primers facing outwards from the LTRs and reverse transcriptase (RT) domain of the retrotransposon. The primers generated specific amplification patterns showing the universal applicability of this marker type. The I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 26 publications
3
47
2
3
Order By: Relevance
“…teo et al (26) tested the transferability of barley-derived Rtn markers in Musa genome and used RTNs for identification, characterization and classification.…”
Section: Caspius and C Gilanicus The Results Of This Study Documentementioning
confidence: 99%
See 1 more Smart Citation
“…teo et al (26) tested the transferability of barley-derived Rtn markers in Musa genome and used RTNs for identification, characterization and classification.…”
Section: Caspius and C Gilanicus The Results Of This Study Documentementioning
confidence: 99%
“…Until DNA extraction, the samples were maintained at greenhouse. Genomics DnA was extracted from leaves of individual plants according to Saghai-Maroof et al IRAP analysis: iRAP analysis was performed according to the protocol previously detailed (14,15), using ltR primers ( Table 2) derived from barley ltRs (14,16,18,26). PcR was carried out in a 5 µl reaction mixture containing 5 ng genomic DnA, 2.5 µl of "2X taq Master Mix ReD" (Amplicon inc., containing 150 mM tris-hcl ph 8.5, 40 mM (nh 4 ) 2 So 4 , 3 mM Mgcl 2 , 0.2% tween 20, 0.4 mM dntPs, 0.05 U/µl taq DnA polymerase, inert red dye and stabilizer), 1.25 pmol of each primer.…”
Section: Methodsmentioning
confidence: 99%
“…Two ISSR primers (3PCT1 and 3PCT2) from Wiesner et al (2001), and a set of six IRAP primers: Sukula, Nikita, 3 0 LTR, 5 0 LTR, LTR6149 and LTR6150 (Kalendar et al 2006;Teo et al 2005;Saeidi et al 2008) were used (Table S2). After tests with some genotypes and optimization of annealing temperature, two ISSR and six IRAP primers giving clear and polymorphic patterns were used for further analysis of DNA from single plants of the accessions.…”
Section: Dna Isolation Issr and Irap-pcr Analysismentioning
confidence: 99%
“…Primers amplifying DNA between SSRs (inter simple sequence repeat, ISSR), retroelements (inter retroelement amplified polymorphisms, IRAP) or SSRs and retroelements (retrotransposon-microsatellite amplification polymorphism, REMAP) have proved to be valuable as informative and polymorphic markers (Kalendar and Schulman 2006;Teo et al 2005;Alsayied et al 2015). Both SSR (evolving by slippage replication or recombination) and retroelements (amplifying through an RNA intermediate and reinserting in the genome) can evolve rapidly and hence show polymorphisms in germplasm with little diversity.…”
Section: Introductionmentioning
confidence: 99%
“…In order to perform IRAP analysis, 21 combinations of LTR primer pairs derived from barley (Hordeum vulgare; Kalendar et al 1999Kalendar et al , 2000Manninen et al 2000;Boyko et al 2002) and banana (Reverse TY1; Teo et al 2005) were tested, from which eight primer combinations showed scoreable bands on 2% agarose gels. These were used for IRAP analysis.…”
Section: Inter Retroelemt Amplified Polymorphisms (Iraps)mentioning
confidence: 99%